Régiók az ezredfordulón? A terhes örökség és a jövő modernizációs kihívásai - Pálné Kovács, Ilona (Tér és Társadalom, 1999)
The perspective of Hungarian administration can only be outlined. Its formation is depending primarily on internal political and professional political decisions and just partly on requirements of the European Union. Strategy of region development can't build on the negative campaign against counties. It is unverifiable at all that regions of regional development could become political units, or Hungarian state-political mechanism could admit regions in place of counties. At present strategy of region development can build on the basis of co-operation between counties – a stronger co-operation than now. The association between regions being indispensable for regional development and strong governmental counties is now the only possible way to satisfy the effectiveness requirements of regional policy and democratic demands of decentralised statehood.